Computational fluid dynamics and trigeminal sensory examinations of empty nose syndrome patients. (9th March 2017) - Li, Chengyu; Farag, Alexander A.; Leach, James; Deshpande, Bhakthi; Jacobowitz, Adam; Kim, Kanghyun; Otto, Bradley A.; Zhao, Kai
Abstract : Objective: The precise pathogenesis of empty nose syndrome (ENS) remains unclear. Various factors such as nasal aerodynamics and sensorineural dysfunction have been suspected, although evidence is limited. This study reported the first examination of both nasal aerodynamics and trigeminal sensory factors in actual ENS patients. Study Design: Prospective case control. Methods: We enrolled six patients diagnosed with ENS. Three patients had pre‐ and post‐inferior turbinate (IT) reduction computed tomography scans, which allowed comparison of their nasal aerodynamics changes through computational fluid dynamic (CFD) simulation. Their symptoms were confirmed through Sino‐nasal Outcome Test‐22, ENS 6‐item Questionnaire, acoustic rhinometry, and rhinomanometry findings. Nasal trigeminal sensitivity that potentially mediates their perception of airflow was assessed via menthol lateralization detection thresholds (LDT) and compared with 14 healthy controls. Results: Post‐surgical reductions in nasal resistance were observed and significantly lower than normal ( P < 0.05). Computational fluid dynamic analysis showed that, paradoxically for all ENS patients, IT reduction did not draw more airflow to the airway surrounding the ITs, but rather resulted in nasal airflow forming into a narrow jet toward the middle meatus region, leaving the airway surrounding the IT with significantly reduced airflow intensity and air–mucosal interactions (inferior region flow percentage reduced from 35.7% ± 15.9% to post‐surgery 17.7% ± 15.7%, P < 0.05; inferior wall‐shear‐stress reduced from 7.5 ± 4.2 × 10 −2 Pa to 3.4 ± 3.1 × 10 −2 Pa, P < 0.01). Empty nose syndrome patients also had significantly impaired menthol LDT compared to healthy controls ( P < 0.005). Conclusion: The results indicated that a combinatory of factors, including paradoxically distorted nasal aerodynamic, impaired sensorineural sensitivity, and potential predisposing conditions, may contribute to the development of ENS. Level of Evidence: 3b. Laryngoscope, 127:E176–E184, 2017